2016
DOI: 10.1103/physrevb.93.195303
|View full text |Cite
|
Sign up to set email alerts
|

Surface phase, morphology, and charge distribution transitions on vacuum and ambient annealedSrTiO3(100)

Abstract: The surface structures of SrTiO 3 (100) single crystals were examined as a function of annealing time and temperature in either oxygen atmosphere or ultra-high vacuum (UHV) using noncontact atomic force microscopy (NC-AFM), Auger electron spectroscopy (AES), and low-energy electron diffraction (LEED). Samples were subsequently analyzed for the effect the modulation of their charge distribution had on their surface potential. It was found that the evolution of the SrTiO 3 surface roughness, stoichiometry, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 71 publications
2
36
0
Order By: Relevance
“…Along [001] the material is constructed of alternating TiO 2 and SrO planes with the SrO planes resembling a single (001) plane of rock salt‐structured SrO. Under the preparation conditions employed here, the surface displays a predominant TiO 2 termination . Meanwhile, SnTe forms a rock salt structure with a 0.6325 nm lattice constant at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along [001] the material is constructed of alternating TiO 2 and SrO planes with the SrO planes resembling a single (001) plane of rock salt‐structured SrO. Under the preparation conditions employed here, the surface displays a predominant TiO 2 termination . Meanwhile, SnTe forms a rock salt structure with a 0.6325 nm lattice constant at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The pattern in Figure a for the SrTiO 3 substrate reveals strong (1 × 1) spots with a trace of a c (2 × 2) reconstruction. This pattern was recorded after subliming away a thick SnTe film at 800 K; since the SrTiO 3 surface is unaffected by annealing at 800 K in UHV (ultra‐high vacuum) for 30 min, the pattern reflects the surface state prior to growth even though the measurement was not performed in the growth chamber. The LEED pattern for a 400 uc SnTe film before it was sublimed away in Figure b shows that the substrate spots are replaced by a new, more compressed square pattern; there is no longer any evidence of a reconstruction; the [10] direction of the film surface matches that of the substrate; and that the diffraction features appear as arcs with an ≈15° spread.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we follow the process of 30 min vacuum annealing steps as thoroughly investigated by Dagdeviren et al. 1 Under these conditions no changes in the step density of the STO(001) surface was observed, while the increased density of oxygen vacancies lead to a change in surface reconstructions. In contrast to this work we did not perform extensive ex-situ cleaning steps involving either oxygen annealing and/or acid treatment required to achieve large, regular terraces.…”
Section: S5 Sto Surface Characterisationmentioning
confidence: 99%
“…In the following, we focus on stoichiometry changes of the very surface of SrTiO 3 upon thermal reduction. It has been reported that annealing under reducing conditions leads to the evolution of a Ti‐rich surface with new reconstruction and eventually Ti 2 O 3 or TiO islands can form on the surface . In general, two different channels changing the chemical composition of the surface have to be taken into account, namely segregation and sublimation .…”
mentioning
confidence: 99%